EFEKTIVITAS QUIZIZZ DALAM OPTIMALISASI EVALUASI MATA KULIAH - Pane, Betharia (Jurnal Lazuardi, 2025)
This paper discusses the utilization of the educational application Quizizz to optimize learning evaluation at the Faculty of Teacher Training and Education, Nusa Cendana University. As civil servants (ASN), lecturers are required to master digital technology in line with the Smart ASN vision. Traditional evaluation methods have been identified to possess several drawbacks, such as delayed feedback, time-consuming assessment processes, and limited capacity to measure holistic competencies. To address these issues, a program utilizing Quizizz has been designed to facilitate more interactive, efficient, and environmentally friendly evaluations. This application features gamification elements, such as points and attractive visuals, which can enhance student motivation. Moreover, Quizizz's automatic reporting capabilities allow lecturers to analyze learning outcomes more quickly and accurately. This implementation is expected to serve as a strategic step toward developing effective technology-based evaluation methods, supporting the Smart ASN vision, and improving the quality of learning in the digital era.